THE INFLUENCE OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE AND PERCEIVED ENJOYMENT TO INTENTION TO USE ELECTRONIC MONEY IN MANADO - Sigar, Junita Fadhillah (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Electronic payment besides phone banking, internet banking, debit or credit card but recently in Indonesia has developed other electronic payment products called Electronic Money. The purpose of this study was to find out the influences between perceived usefulness, perceived ease of use, perceived enjoyment on intention to use electronic money especially to customer of electronic money in Manado city. This research is quantitative researches that use casual type of research. The data was collected through questionnaire with sample size is about 60 respondents who are selected using convenience sampling method and analyzed by multiple linear regression analysis method. The result of this research reveals that there is significant positive influence between perceived usefulness, perceived ease of use and perceived enjoyment to intention to use electronic money. The issuer of electronic money banks or non-banks should increase the knowledge about the electronic money products through the advertisement and promotion and also by make socialization about the product to the public. So the public can know the usefulness and how to use electronic money as a payment instrument. Keywords: perceived usefulness, perceived ease of use, perceived enjoyment, electronic money